Short-term Effects of Kaltenborn-Evjenth Functional Glide on Pain, ROM, and Function in Patients with Breast Cancer - Lee, Hyunah; Seo, Dongkwon (Physical therapy rehabilitation science, 2024)
Objective: The purpose of this study was to investigate the effect of Kaltenborn–Evjenth concept functional glide (KEFG) on shoulder pain, range of motion (ROM), upper extremity dysfunction in breast cancer patients. Design: Cross-sectional study. Methods: In this study, 42 subjects were randomly assigned and distributed to 21 subjects in the KEFG group and 21 subjects in the Mulligan technique (MWM) group. Results: After the application of joint mobilization, pain decreased significantly in both groups, and there was no significant difference between the two groups. The ROM of the joint was significantly increased in both groups, and there was no significant difference between the two groups. The SPADI pain was significantly decreased in both groups, and the disability and total components were significant only in the KEFG group, and there was no significant difference between the two groups. Conclusions: KEFG and MWM were found to be effective in improving shoulder pain, ROM and upper extremity dysfunction in breast cancer patients. KEFG is thought to be an intervention that can yield positive outcomes among breast cancer patients with upper extremity dysfunction. KCI Citation Count: 0